A multilevel investigation of factors related to achievement in Ireland and Spain using PISA data - Frade-Martínez, Cristina; O’Hara, Joe; Gamazo, Adriana; Olmos-Migueláñez, Susana; Brown, Martin (Frontiers in Education, 2024)
The Programme for International Assessment (PISA) is a methodology for making comparative judgements about the quality of education systems. Celebrated by proponents as a transparent process that allows policy makers produce data informed judgments about relative quality of their national education system PISAand through it the OECDhas become a key vehicle for informing and explaining educational policy development. This paper explores the Irish and Spanish outcomes of the 2018 round of PISA. It examines the contextual factors that are associated with performance at student and school level while at the same time developing a multi-level statistical model to explain divergent school performance profiles It finds that issues associated with the socio-economic level of the students, the repetition rate, and student age are common across all domains in both countries. It suggests that the socio-economic status of Spanish students at school level is not significant, that the shortage of teachers in Ireland affects student performance, and that immigrant status does not disadvantage Spanish student performance. It concludes by suggesting that studies involving a wider application of the model be undertaken to assess possible social, economic, and cultural causes that may explain the differences in variable significance in each country.